The Role of Value Co-Creation On School Image and Parent Loyalty - Ardiana Kurniasari; Christian Herdinata; Burhan Bungin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Increasing competition among educational institutions and the growing involvement of parents in educational services have encouraged schools to adopt more collaborative and value-oriented strategies. However, empirical evidence on how parental value co-creation behavior contributes to school image and parental loyalty, particularly in the context of basic education, remains limited. This study investigates the role of parental value co-creation behavior in shaping school image and fostering parental loyalty in elementary education. Drawing on service-dominant logic, an integrated conceptual framework is proposed in which parental value co-creation behavior influences parental loyalty both directly and indirectly through school image. Data were collected from parents of elementary school students in Surabaya, East Java, Indonesia. A total of 370 online questionnaires were distributed, with 170 valid responses analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that both parental participation behavior and parental citizenship behavior have a significant positive effect on school image. Furthermore, school image is found to positively influence parental loyalty and to mediate the relationship between value co-creation behavior and loyalty. These findings suggest that schools that actively encourage and facilitate parental involvement are able to create a supportive and collaborative educational environment, thereby strengthening institutional image and enhancing parental commitment. This study contributes to the limited literature on value co-creation in basic education by empirically demonstrating the mediating role of school image. Practically, the findings highlight the strategic importance of parental involvement as an educational marketing approach to improve school reputation and stimulate positive word-of-mouth. Future studies may involve other stakeholders and explore different regional contexts.